THE INFLUENCE OF WORK MOTIVATION AND WORK DISCIPLINE ON THE EFFECTIVENESS OF EMPLOYEE WORK IN THE DIRECTORATE WORK UNIT AT Poltekkes Ministry of Health Jakarta III - Duwi Rahmawati; Sri Siswani; Nurminingsih; Ahmadun (Transpublika Publisher, 2023)
In today's dynamic and competitive business environment, the effective functioning of employees plays a pivotal role in the success of organizations. This study aims to explore and establish explanatory insights regarding the influence of (1) Work Motivation on Employee Work Effectiveness, (2) Work Discipline on Employee Work Effectiveness, and (3) Work Motivation on Work Discipline. Employing a quantitative approach, the research encompasses the entire employee population of the Directorate work unit at Poltekkes Ministry of Health Jakarta III, with a sample size of 55 respondents. Data collection is conducted through a combination of questionnaires and interviews. The findings highlight significant relationships: Work Motivation (X1) demonstrates a substantial correlation with Work Effectiveness (Y) (T-Statistic: 2.206, p > 1.96). The positive original sample estimate of 0.370 underscores the link between Work Motivation (X1) and Work Effectiveness (Y). Similarly, Work Discipline (X2) and Work Effectiveness (Y) exhibit significance (T-Statistic: 3.568, p > 1.96), with an original sample estimate of 0.592 indicating their positive relationship. Notably, the relationship between work motivation (X1) and work discipline (X2) is profoundly significant (T-statistic: 94.559, p > 1.96), supported by an original sample estimate of 0.945, confirming their positive association. In conclusion, this study contributes valuable insights into the interplay of Work Motivation, Work Discipline, and Employee Work Effectiveness within the context of the Directorate work unit at Poltekkes Ministry of Health Jakarta III.